2018
DOI: 10.18632/oncotarget.25473
|View full text |Cite
|
Sign up to set email alerts
|

LRP/LR specific antibody IgG1-iS18 impedes neurodegeneration in Alzheimer's disease mice

Abstract: Alzheimer’s disease (AD) is a neurodegenerative disease caused by accumulation of amyloid beta (Aβ) plaque and neurofibrillary tangle formation. We have shown in vitro, that knock-down and blockade of the 37 kDa/67 kDa Laminin Receptor (LRP/LR) resulted in reduced Aβ induced cytotoxicity and Aβ accumulation. In order to test the effect of blocking LRP/LR on Aβ formation and AD associated symptoms, AD transgenic mice received the anti-LRP/LR specific antibody, IgG1-iS18 through intranasal administration. We sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…As the pursuit of chemical compounds has been resulting in limited success, while two of the approved drugs for AD are naturally derived, extensive research efforts are now being directed toward the investigation of natural compounds (Howes and Perry, 2011). Recently, the intranasal application of an antibody in mice led to the reduction of beta-amyloid (Aβ) accumulation induced cytotoxicity (Ferreira et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…As the pursuit of chemical compounds has been resulting in limited success, while two of the approved drugs for AD are naturally derived, extensive research efforts are now being directed toward the investigation of natural compounds (Howes and Perry, 2011). Recently, the intranasal application of an antibody in mice led to the reduction of beta-amyloid (Aβ) accumulation induced cytotoxicity (Ferreira et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it was found that the IgG1-iS18 antibody-mediated rescuing of cells from cytotoxicity is dependent on PrP c due to the interaction between PrP c and Aβ42 [41]. Recently, an in vivo study, whereby B6SJL-Tg6799 AD transgenic mice were injected with the IgG1-iS18 antibody, confirmed the in vitro findings whereby a decrease in amyloid plaque formation and Aβ42 levels with a concomitant increase in both shortterm and learning memory was observed [42].…”
Section: Introductionmentioning
confidence: 69%
“…Recently, Otgaar et al, [36] found that an overexpression of LRP::FLAG increased both hTERT levels and telomerase activity with a concomitant reduction in senescent markers. Furthermore, Ferreira et al, [42] observed an increase in mTERT in mice treated with the anti-LRP/LR specific antibody, IgG1-iS18 with a concomitant decrease in Aβ peptides and amyloid plaques. In addition, an increase in telomerase activity and hTERT expression was observed with a concomitant reduction in Aβ shedding and intracellular Aβ levels in cells overexpressing LRP::FLAG [58].…”
Section: Introductionmentioning
confidence: 96%
“…LRP/LR also directly interacts with pTau (Cuttler et al, 2020) and modulates Aβ toxicity (Bignoux et al, 2019). An intranasally administered antibody targeted to LRP/LR decreases Aβ plaques and improves memory performances in 5XFAD AD model mouse (Ferreira et al, 2018).…”
Section: Molecular Control Of Oaβ42-dependent Modulation Of Memorymentioning
confidence: 99%